Kesan kecerdasan emosi ke atas tekanan kerja dan niat berhenti kerja profesion perguruan - Syed Sofian Syed Salim,; Rohany Nasir, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
The first aim of this research was to find out the relationship between emotional intelligence and work stress and the desire to leave the teaching profession. Second, it aimed to look at the interaction of four elements in emotional intelligence: self awareness, self management, social awareness, and social skills on two variables: work stress and the intention to leave the teaching profession. A total of 1200 teachers from 60 schools in Malacca, Perak and Pulau Penang were chosen as the repondents of this study which was conducted in the middle of 2007. A set of questionnaire consisting of: Emotional Competence Inventory (ECI) was utilized to measure emotional intelligence, the Occupational Stress Indicator (OSI) to measure work stress and the Propensity To Leave Index (PLI) to measure the intention to leave the teaching profession was used. Research findings obtained through the Pearson correlation analysis revealed a positive and significant relationship between emotional intelligence and the intention to leave the teaching profession. In contrast, there was a negative but significant relationship between emotional intelligence and stress. The result of the Multiple Regression Analysis indicated that the value of four dimensional coefficient correlation in emotional intelligence on the intention to leave the teaching profession was positive and significant. Meanwhile there was a positive and insignificant four dimensional coefficient correlation with work stress